Early Knee Osteoarthritis Is Evident One Year Following Anterior Cruciate Ligament Reconstruction: A Magnetic Resonance Imaging Evaluation. Issue 4 (April 2015) - Culvenor, Adam G.; Collins, Natalie J.; Guermazi, Ali; Cook, Jill L.; Vicenzino, Bill; Khan, Karim M.; Beck, Naomi; van Leeuwen, Janneke; Crossley, Kay M.
Abstract : Objective: To determine the prevalence and factors associated with knee osteoarthritis (OA) defined by magnetic resonance imaging (MRI) and specific OA features on MRI 1 year after anterior cruciate ligament reconstruction (ACLR). Methods: Isotropic 3.0T MRI scans were obtained for 111 participants (71 men; mean ± SD age 30 ± 8 years) 1 year after ACLR as well as for 20 age‐, sex‐, and activity level–matched uninjured controls. The MRI OA Knee Score was used to score specific OA features. MRI‐defined tibiofemoral and patellofemoral OA was evaluated based on published criteria. Logistic regression identified factors associated with MRI‐defined OA and specific OA features after ACLR. Results: Following ACLR, medial and lateral tibiofemoral OA on MRI was observed in 7 participants (6%) and 12 participants (11%), respectively, while 19 participants (17%) had patellofemoral OA on MRI. The femoral trochlea was the region most affected by bone marrow lesions (19% of participants), cartilage lesions (31% of participants), and osteophytes (37% of participants). Meniscectomy at the time of ACLR (odds ratio 6.8 [95% confidence interval 2.0–23.3]) and body mass index (BMI) >25 kg/m 2 (odds ratio 3.0 [95% confidence interval 1.3–6.9]) predicted MRI‐defined tibiofemoral OA and osteophytes, respectively. Men had higher odds of patellofemoral osteophytes (odds ratio 6.3 [95% confidence interval 2.4–16.2]). No uninjured controls had tibiofemoral or patellofemoral OA on MRI, and specific OA features were uncommon. Conclusion: OA 1 year following ACLR was more common than previously recognized, while being absent in uninjured control knees. The patellofemoral compartment seems to be at particular risk for early OA after ACLR, especially in men. The association with meniscectomy and BMI demonstrates the construct validity of MRI criteria.